Ultraviolet photoconduction in tungsten disulphide based Schottky heterostructure photodetector - Ahmad, Harith; Thandavan, Tamil Many K. (Elsevier, 2019)
A proposed Ag/WS2/SiO2/p-Si/Ag Schottky heterostructure photodetector is tested for its photoconduction behaviour under ultraviolet (UV) illumination using a light emitting diode (LED) at 380 nm. This is done at various illumination powers as well as different direct current (DC) bias voltages. A simple and feasible drop casting method and heating process allows good adhesion of tungsten disulphide (WS2) onto a silicon dioxide/p-silicon (SiO2/p-Si) substrate forming a Schottky contact. In order to enhance photoconduction, iron (Fe) powder is introduced to build contacts between WS2 and the substrate. Field emission scanning electron microscope (FESEM) analysis, energy dispersive x-ray (EDX) spectroscopy and x-ray diffraction (XRD) results confirm the formation of the WS2 thin film. Raman spectrum peaks at 357 cm−1 (E1 2g) and 417 cm−1 (A1g) confirm the presence of WS2 while peaks 214, 223, 274 and 292 cm−1 and a small broad shoulder at 694 cm−1 confirm the presence of iron (III) oxide (Fe2O3). Furthermore, profound D and G bands at 1370 and 1585 cm−1 respectively indicate defected carbon (C) structures in the WS2 thin film. Excellent photoconduction of UV LED 380 nm light source showed power and DC bias voltage dependent characteristics. Wide variations in rise and fall time justifies that the device can be operated at selected bias voltages and frequency modulations. © 2019